High-heat-resistant flame-retardant polyurethane resin and preparation method thereof

By introducing TBPA and VDT copolymers into the polyurethane optical resin, a high heat-resistant flame-retardant polyurethane resin was prepared, which solved the problem of insufficient flame-retardant and heat-retardant performance of existing materials in extreme cases and achieved wider application.

CN119390924AActive Publication Date: 2025-02-07WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411729668.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-07
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Existing polyurethane optical resins lack flame retardant and heat resistance in extreme cases (such as fire or high temperature environments) and cannot meet certain special needs.

Method used

Flame retardant polymers were prepared by introducing tetrabromobenzene A diallyl ether (TBPA) and 2-vinyl-4,6diamino-1,3,5-triazine (VDT) into polyurethane resins to copolymerize. , and mix it with isocyanate components and polymerized thiol compounds to form a highly heat-resistant flame-retardant polyurethane resin.

Benefits of technology

The high heat resistance and flame retardant properties of polyurethane optical resin are achieved, improving the safety and application range of materials, especially in extreme environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390924A_ABST
    Figure CN119390924A_ABST
Patent Text Reader

Abstract

The invention provides a high-heat-resistance flame-retardant polyurethane resin and a preparation method thereof, the resin comprises a flame-retardant polymer, the flame-retardant polymer is formed by copolymerization of a tetrabromobisphenol A diallyl ether (TBPA) monomer and a 2-vinyl-4, 6-diamino-1, 3, 5-triazine (VDT) monomer, and the resin also comprises the following raw materials: isocyanate, a polythiol compound and the like. The polyurethane resin material disclosed by the invention not only has flame retardant property, the limit oxygen index LOI value can reach 32, but also improves the glass-transition temperature of the resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of optical resins, and in particular to a highly heat-resistant and flame-retardant polyurethane resin and a preparation method thereof. Background Art

[0002] Polyurethane optical resin is mainly made by casting isocyanate and polythiol. Its characteristic is that the refractive index of the lens can be adjusted by selecting different isocyanates and polythiol. Taking the MR series of commercially available products as an example, MR-7 is an optical lens with a refractive index of 1.67, MR-8 is an optical lens with a refractive index of 1.60, and MR-174 is an optical lens with a refractive index of 1.74. Based on this, customers can choose suitable lenses according to the price and personal needs.

[0003] With the development of the information age, consumers' demands for lenses have become more diversified, such as high-impact lenses that meet sports needs, anti-fog lenses that meet the needs of medical workers, and so on. From a safety perspective, consumers are beginning to demand flame-retardant and highly heat-resistant resin lenses to meet needs in extreme situations. For example, people who work for a long time in a fire or high-temperature environment require materials with high heat resistance and flame retardancy. Specifically, high heat resistance is mainly for the glass transition temperature (Tg) of the material, because for polymer materials, the glass transition temperature is the temperature at which the chain segments in the polymer material begin to move. Above the Tg temperature, the modulus of the lens material drops sharply and is prone to deformation. Taking the commercially available MR-10 and MR-7 as examples, the glass transition temperature of MR-10 is 100°C, and MR-7 is only 85°C, so it can be seen that MR-10 has better heat resistance. At present, the Tg temperature range of polyurethane optical resins is roughly 70-120°C. The main reason for the difference is the different chemical structures of the isocyanate component and the polythiol.

[0004] Flame retardant additives are modifiers that can be added to flammable materials to block the occurrence of fire and suppress the extent of fire. They mainly include halogen, phosphorus flame retardants, organic flame retardants, inorganic flame retardants and composite modified flame retardants. Adding halogen atoms such as bromine to organic materials is the main way to give materials flame retardant properties. The LOI value (Limiting Oxygen Index) is an indicator to measure the flame retardant properties of materials. It indicates the minimum oxygen concentration (volume percentage) required for the material to maintain balanced combustion in a mixture of nitrogen and oxygen under specified conditions. The higher the LOI value, the better the flame retardant properties of the material. Since resin materials are organic polymer materials, the LOI value is generally below 22, which belongs to the flammable grade. For example, the LOI of polymethyl methacrylate (PMMA) optical resin is only 17.5. If the LOI value is above 22, it means that the material has different degrees of flame retardant properties. Specifically, if the LOI value is in the range of 22-26, the material is difficult to burn, indicating that it has certain flame retardant properties. If the LOI value is in the range of 26-40, the material is difficult to burn, indicating that it has good flame retardant properties. If the LOI value is above 40, the material is not easy to burn, indicating that it has good flame retardant properties.

[0005] Patent CN115124825A provides users with a flame-retardant resin material by coating the surface of polycarbonate (PC) material, but does not modify the chemical structure of the material itself. Patent CN105778094A introduces phosphorus-containing compounds and uses polyacrylate phosphate compounds and polythiol compounds for curing reaction to obtain flame-retardant optical resins, which are used to solve the problem that existing LED packaging resins such as epoxy resins and silicone resins are not flame-retardant and have fire hazards. The flame-retardant optical resin prepared by this patent meets the requirements of LED packaging resins for flame retardancy and refractive index. However, the acrylate phosphate compounds mentioned in this patent are not suitable for polyurethane optical resin materials. Excessive acrylate phosphate compounds are prone to cause side reactions such as polyurethane foaming, which cannot meet application requirements.

[0006] Therefore, in order to promote the diversified development of polyurethane materials and meet the needs of some consumers, it is necessary to develop highly heat-resistant and flame-retardant polyurethane optical resins. Summary of the invention

[0007] In view of the above-mentioned problems, the present invention provides the following technical solutions:

[0008] The object of the present invention is to provide a highly heat-resistant and flame-retardant polyurethane resin and a preparation method thereof. The polyurethane resin of the present invention not only has conventional optical properties, but also has excellent flame retardant properties and heat resistance.

[0009] To solve the above problems, the present invention provides a highly heat-resistant flame-retardant polyurethane resin, comprising a flame-retardant polymer, which is prepared by copolymerizing tetrabromobisphenol A bisallyl ether (TBPA) monomer and 2-vinyl-4,6-diamino-1,3,5-triazine (VDT) monomer.

[0010] The flame retardant polymer is prepared by dissolving tetrabromobisphenol A bisallyl ether (TBPA) monomer containing halogen bromine atoms and 2-vinyl-4,6-diamino-1,3,5-triazine (VDT) monomer in an organic solvent, and then performing free radical polymerization under the condition of a free radical initiator.

[0011] Preferably, the free radical initiator is an organic peroxide compound initiator, an azo compound initiator, a redox system initiator or a photosensitive initiator; the organic peroxide compound initiator is selected from dibenzoyl peroxide (BPO) or peroxydicarbonates, the azo compound initiator is selected from azobisisobutyronitrile (AIBN) or azobisisoheptanenitrile (ABVN), the redox system initiator is selected from an organic oil-soluble redox system formed by a peroxide acyl compound and a tertiary amine compound, and the photosensitive initiator is selected from photoinitiator IRGACURE-2959, etc.

[0012] Preferably, the added amount of the initiator is 1%-6% of the total weight of the tetrabromobisphenol A bisallyl ether (TBPA) monomer and the 2-vinyl-4,6-diamino-1,3,5-triazine (VDT) monomer.

[0013] Further preferably, the free radical initiator is a composite initiator of dibenzoyl peroxide (BPO) and N,N-dimethylaniline (DMA), and the addition amount of both is 1%-3%, preferably 1.5-2.5%, of the total weight of TBPA and VDT.

[0014] Preferably, the reaction temperature is 0°C to 50°C, and the reaction time is 1 to 12 hours. More preferably, the reaction temperature is room temperature (25°C ± 5°C), and the reaction time is 2 to 4 hours.

[0015] The molar ratio of TBPA monomer to VDT monomer is 1:1-20:1, preferably 3:1-15:1, and more preferably 5:1-10:1.

[0016] The organic solvent is an organic solvent that can fully dissolve the TBPA monomer and the VDT monomer, and can stably exist without chemical reaction, and specifically includes but is not limited to the following organic solvents: halogenated hydrocarbons such as chlorobenzene, ketones such as acetone, ethers such as methyl tert-butyl ether, alcohols such as ethanol, amides such as dimethylformamide, sulfones such as dimethyl sulfoxide, etc., preferably dimethyl sulfoxide.

[0017] The high heat-resistant flame-retardant polyurethane resin of the present invention comprises an isocyanate component, a polythiol compound, a flame-retardant polymer, a catalyst, an optional mold release agent and an optional ultraviolet absorber.

[0018] The isocyanate component of the present invention is not particularly limited and can be selected from aliphatic, alicyclic or aromatic isocyanates. Specific examples of the isocyanate component include but are not limited to toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, naphthalene diisocyanate, dimethylbiphenyl diisocyanate, 1,4-cyclohexane diisocyanate, p-phenylene diisocyanate, tetramethyl-m-xylylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, xylylene diisocyanate, cyclohexane dimethylene diisocyanate, and a combination of one or more of norbornane diisocyanate, preferably xylylene diisocyanate or cyclohexane dimethylene diisocyanate, and more preferably xylylene diisocyanate.

[0019] The polythiol compound described in the present invention is not particularly limited. As a specific example of the polythiol compound, for example but not limited to, the polythiol compound is selected from ethylene glycol dithioacetate, 1,2-bis(2-mercaptoethoxy)ethane, di(thioglycolic acid)-1,4-butylene glycol, trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tris(2-mercaptoacetate), pentaerythritol tetramercaptoacetate, 2,3-dithio(2-mercapto)-1-propanethiol, tetrakis(3-mercaptopropionic acid) pentaerythritol ester and one or more thereof, preferably 2,3-dithio(2-mercapto)-1-propanethiol or tetrakis(3-mercaptopropionic acid) pentaerythritol ester, more preferably 2,3-dithio(2-mercapto)-1-propanethiol.

[0020] In order to increase the degree of reaction of the functional groups, the molar ratio of NCO group / SH group in the isocyanate component and the polythiol compound is controlled in the range of 0.8-1.5, preferably 0.9-1.1.

[0021] The flame retardant polymer is added in an amount of 0.1% to 10% by weight, preferably 0.5% to 8% by weight, and more preferably 1% to 6% by weight, based on the total mass of the isocyanate component and the polythiol compound.

[0022] Adding the flame-retardant polymer described in the present application to the polyurethane resin can not only make the polyurethane optical resin have flame-retardant properties, but also effectively bond the amino groups and NCO groups in the large molecular weight flame-retardant polymer, enhance the compatibility of the additive with the matrix resin, improve the thermal stability of the resin, and prevent abnormal phenomena such as the loss of additives in the resin lens caused by the direct addition of TBPA monomer.

[0023] It is also necessary to add a catalyst, an optional ultraviolet absorber, an optional mold release agent, etc. to the polyurethane resin.

[0024] The catalyst may be a catalyst commonly used in the art, such as an organotin compound, as a specific example, dialkyl tin halides such as dibutyltin dichloride and dimethyltin dichloride, dialkyl dicarboxylates such as dimethyltin diacetate, dibutyltin dioctoate, and dibutyltin dilaurate, preferably dibutyltin dichloride. Based on the total mass of the isocyanate component and the polythiol compound, the amount of the catalyst added is 0.001 to 2.0% by weight, preferably 0.005 to 1.0% by weight.

[0025] The organic products selected as ultraviolet absorbers are mainly divided into benzophenones, triazines and benzotriazoles, among which benzophenones have weak absorption and triazines have poor stability, so benzotriazoles are often used for industrial production. Taking benzotriazoles as an example, benzotriazole ultraviolet absorbers, specifically UV49, UV326, UV 327, UV 360, UV 380, UV 329, preferably UV 329 (trade name Tinuvin 329), are added in an amount of 0.001-2.0% by weight, preferably 0.01 to 1.0% by weight, based on the total mass of the isocyanate component and the polythiol compound.

[0026] Due to the special requirements of optical resins for light transmittance, a phosphate-based mold release agent with a trade name of Zelec UN is selected as the mold release agent. The addition amount is 0.01-3.0 wt %, preferably 0.05 to 2.0 wt %, based on the total mass of the isocyanate component and the polythiol compound.

[0027] The present invention also provides a method for preparing the polyurethane resin, which is prepared by mixing an isocyanate component, a polythiol compound, a flame retardant polymer, an optional catalyst, an optional optical resin release agent, and an optional ultraviolet absorber and then subjecting the mixture to a polymerization reaction. The flame retardant polymer is preferably first ground into powder and then added to the reaction.

[0028] The present invention can adopt the existing preparation process of polyurethane optical resin by polymerization reaction of isocyanate and polythiol compound, which is well known in the art, and the preparation process mainly includes stirring and mixing the components in the raw material composition, and then degassing and curing to obtain the polyurethane optical resin. The curing process needs to be slowly heated from low temperature to high temperature, for example, from room temperature to 100-120°C, so that it is polymerized and cured, and then demolded after secondary curing to obtain the polyurethane material.

[0029] The high heat-resistant and flame-retardant polyurethane resin of the present invention can be applied to optical resins.

[0030] In the flame-retardant polymer of the present invention, the introduction of the halogen bromine element can realize the flame-retardant property of the material, and the amino group in the VDI monomer realizes chemical bonding with the isocyanate component NCO, which can realize the effective addition of the flame-retardant polymer PTBPA-PVDT in the polyurethane resin system without affecting the optical properties of the polyurethane resin.

[0031] The glass transition temperature Tg and limiting oxygen index LOI value of the high heat-resistant flame-retardant polyurethane optical resin obtained by the preparation method of the present invention show certain differences according to the addition of different contents of flame-retardant polymers. Generally speaking, within a certain range, as the amount of flame-retardant polymer added increases, the Tg and LOI values ​​are higher. In the polyurethane resin prepared by m-xylylene diisocyanate within the test range, when the amount of flame-retardant polymer added is 9wt%, the Tg and LOI values ​​are 32°C and 137°C, respectively. Therefore, according to the preparation method of the present invention, a high heat-resistant flame-retardant polyurethane optical material with excellent performance can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The flame retardant polymer (PTBPA-PVDT) prepared in Example 1 1 H-NMR spectrum. DETAILED DESCRIPTION

[0033] The present invention is further illustrated by the following examples, but the scope of protection of the present invention is not limited thereto.

[0034] The following examples of the present invention will be analyzed and characterized using the following instruments.

[0035] Gel permeation chromatography analysis: Gel permeation chromatography characterization of copolymer macromolecules was performed using an Agilent 1260 high performance liquid gel permeation chromatograph. The sample was dissolved in tetrahydrofuran (THF) to prepare a solution with a concentration of 4 mg / mL, and tested on the GPC instrument with a differential detector, an elution rate of 1 mL / min, and a column temperature of 35°C.

[0036] H-NMR spectrum analysis: The H-NMR spectrum of the copolymer was characterized by using a Varian INOVA H-NMR spectrometer (500 MHz). 5-10 mg of the sample was dissolved in deuterated dimethyl sulfoxide (DMSO), and the solution was mixed evenly and then 1H-NMR was tested using an NMR spectrometer.

[0037] Analysis of optical resin application indicators: The light transmittance is Hunterlab USVIS1839 colorimeter, the test light source is C / 2 light source, the test mode is total transmission, and the average transmittance in the wavelength range of 380nm to 780nm is taken as the sample transmittance. In addition, the yellowness index (YI value) of the sample is tested under the same mode. For optical lenses, the higher the transmittance, the smaller the reflection and absorption, and the clearer the optical material. At the same time, the smaller the YI value, the better the hue of the plastic lens, and the larger the YI value, the worse the hue becomes. GB 10810.3-2006 "Spectacle lenses and related eyewear products Part 3: Transmittance specifications and measurement methods" requires the transmittance in the visible light spectrum region (380nm to 780nm) to be unified as 80% and above. GB 2506-2001 has the following standard requirements for the YI value: when the refractive index of the lens is ≥1.56, YI≤2.20; when the refractive index of the lens is <1.56, YI≤1.20.

[0038] The glass transition temperature Tg was tested using a Mettler-Toledo high pressure differential scanning calorimeter (METTLER HPDSC1). The DSC test method was: 30°C-300°C, temperature scanning, a heating rate of 10°C / min, a nitrogen atmosphere, and a nitrogen flow rate of 50 ml / min. Each sample was tested 3 times in parallel and the average value was taken.

[0039] Limiting oxygen index (LOI) test: According to GB / T2406.2-2009, 4mm specimens are used. The oxygen index tester is Hebei Fangyuan Instrument Equipment Co., Ltd., model JF-3.

[0040] The samples of polyurethane optical resin used to test the optical properties are all prepared by a fixed mold (the fixed mold is a flat-bottomed glass cup with a bottom diameter of 500mm and a height of 800mm). The materials required for the flame retardant performance test are selected according to GB / T2406.2-2009. 4mm specimens.

[0041] The main raw materials are:

[0042] m-Xylylene diisocyanate (XDI, NCO content 44.7%, purity ≥99.5%, Wanhua Chemical, brand XR-2005), cyclohexane dimethylene diisocyanate (H 6 XDI, NCO content is 43.3%, purity ≥99.7%, Wanhua Chemical, brand XR-2006), hexamethylene diisocyanate (HDI, NCO content is 49.8%, purity ≥99.5%, Wanhua Chemical), isophorone diisocyanate (IPDI, NCO content is 37.8%, purity ≥99.5%, Wanhua Chemical)

[0043] The polythiol compounds selected are 2,3-dithio (2-mercapto)-1-propanethiol (trade name polythiol 504, purity ≥ 98%, Shandong Yifeng), tetrakis (3-mercaptopropionic acid) pentaerythritol ester (trade name polythiol 405, purity ≥ 98%, Shanghai Aladdin Biochemical Technology Co., Ltd.)

[0044] The catalyst was dibutyltin dichloride (DBC, purity 96%, Sigma-Aldrich)

[0045] Internal release agent (trade name: Zelec UN, Sigma-Aldrich, purity: 98%)

[0046] Ultraviolet absorber UV-329 (trade name TINUVIN 329, purity 98%, Shanghai Aladdin Biochemical Technology Co., Ltd.)

[0047] Tetrabromobisphenol A bisallyl ether (purity 99%, Tianjin Xiensi Biochemical Technology Co., Ltd.)

[0048] 2-vinyl-4,6-diamino-1,3,5-triazine (purity 95%, TCI (Shanghai) Chemical Industry Development Co., Ltd.).

[0049] Example 1

[0050] A highly heat-resistant and flame-retardant polyurethane optical resin containing 5 wt % PTBPA-PVDT copolymer (the monomer molar ratio of TBPA to VDT is 6:1) was prepared.

[0051] (1) Synthesis of PTBPA-PVDT polymer.

[0052] 37.44g of tetrabromobisphenol A bisallyl ether (TBPA) and 1.37g of 2-vinyl-4,6-diamino-1,3,5-triazine (VDT) were added to the reaction vessel in sequence, and then 98g of dimethyl sulfoxide (DMSO) was added as solvent, and the monomer was completely dissolved by stirring at room temperature. Then 0.776g of dibenzoyl peroxide (BPO) was added to the mixed solution, and after stirring and dissolving completely, 0.776g of N, N-dimethylaniline (DMA) was added dropwise, and the mixture was stirred and reacted at room temperature for 3 hours. The addition amount of BPO and DMA was 2wt% of the total mass of tetrabromobisphenol A bisallyl ether (TBPA) and 2-vinyl-4,6-diamino-1,3,5-triazine. After the reaction was completed, the mixture was filtered to collect the filter cake, and the filter cake was washed with methanol for three times, 50ml each time. Finally, the filter cake was vacuum dried at room temperature to obtain PTBPA-PVDT. The number average molecular weight Mn of the PTBPA-PVDT copolymer was tested by gel permeation chromatography (GPC) and was about 37,000, and the polydispersity coefficient PID was 1.36, indicating that the monomer had undergone polymerization. The structural composition of the macromolecule was further tested by hydrogen nuclear magnetic resonance (deuterated DMSO was used as the solvent), as shown in FIG. Figure 1 As shown, it is confirmed that there are two structural units in the molecular chain, thus indicating that the two monomers have been successfully copolymerized. The limiting oxygen index LOI value of the tested polymer is 42.

[0053] (2) Preparation of highly heat-resistant and flame-retardant polyurethane optical resin

[0054] At room temperature, add 0.015g of catalyst dibutyltin dichloride, 0.05g of ultraviolet absorber UV-329, 0.1g of internal release agent, 52g of m-xylylene diisocyanate (XDI), and 5g of PTBPA-PVDT copolymer into a stirred reaction vessel, and mix and dissolve. Then, add 48g of 2,3-dithio (2-mercapto)-1-propanethiol and mix them to form a raw material composition. After filtering the raw material composition through a filter membrane, inject it into a special mold for lens processing (the liquid level of the raw material composition in the mold is about 7mm), and degas for 1 hour at 2kPa or less and 25°C. The pore size of the filter membrane is 1μm.

[0055] After degassing, the temperature was raised from 25°C to 120°C in an oven to polymerize and cure, and the heating rate was set to 0.2°C / min. When the oven temperature reached 120°C, it was maintained for 2 hours to obtain a cured sample. The sample was then naturally cooled to room temperature, and after secondary curing at room temperature for 48 hours, it was demolded to obtain an optical resin material.

[0056] Example 2

[0057] A highly heat-resistant and flame-retardant polyurethane optical resin containing 9 wt % PTBPA-PVDT copolymer (the monomer molar ratio of TBPA to VDT is 2:1) was prepared.

[0058] (1) Synthesis of PTBPA-PVDT polymer.

[0059] 37.44g of tetrabromobisphenol A bisallyl ether (TBPA) and 4.11g of 2-vinyl-4,6-diamino-1,3,5-triazine (VDT) were added to a reaction vessel in sequence, and then 104g of dimethyl sulfoxide (DMSO) was added as a solvent, and the monomers were completely dissolved by stirring at room temperature. Then 0.83g of dibenzoyl peroxide (BPO) was added to the mixed solution, and after stirring to completely dissolve, 0.83g of N, N-dimethylaniline (DMA) was added dropwise, and the mixture was stirred and reacted at room temperature for 3 hours. The addition amount of BPO and DMA was 2wt% of the total mass of tetrabromobisphenol A bisallyl ether (TBPA) and 2-vinyl-4,6-diamino-1,3,5-triazine. After the reaction was completed, methanol washing and vacuum drying were carried out as in Example 1.

[0060] (2) Preparation of highly heat-resistant and flame-retardant polyurethane optical resin

[0061] At room temperature, add 0.015g of catalyst dibutyltin dichloride, 0.05g of ultraviolet absorber UV-329, 0.1g of internal release agent, 52g of m-xylylene diisocyanate (XDI), and 9g of PTBPA-PVDT copolymer into a stirred reaction vessel, and mix and dissolve. Then, add 48g of 2,3-dithio (2-mercapto)-1-propanethiol and mix them to form a raw material composition. After filtering the raw material composition through a filter membrane, inject it into a special mold for lens processing (the liquid level of the raw material composition in the mold is about 7mm), and degas for 1 hour at 2kPa or less and 25°C. The pore size of the filter membrane is 1μm.

[0062] After degassing, the temperature was raised from 25°C to 120°C in an oven to polymerize and cure, and the heating rate was set to 0.2°C / min. When the oven temperature reached 120°C, it was maintained for 2 hours to obtain a cured sample. The sample was then naturally cooled to room temperature, and after secondary curing at room temperature for 48 hours, it was demolded to obtain an optical resin material.

[0063] Example 3

[0064] A highly heat-resistant and flame-retardant polyurethane optical resin containing 0.2 wt % PTBPA-PVDT copolymer (the monomer molar ratio of TBPA to VDT is 18:1) was prepared.

[0065] (1) Synthesis of PTBPA-PVDT polymer.

[0066] 56.16g of tetrabromobisphenol A bisallyl ether (TBPA) and 0.685g of 2-vinyl-4,6-diamino-1,3,5-triazine (VDT) were added to a reaction vessel in sequence, and then 142g of dimethyl sulfoxide (DMSO) was added as a solvent, and the monomers were completely dissolved by stirring at room temperature. Then 1.14g of dibenzoyl peroxide (BPO) was added to the mixed solution, and after stirring and completely dissolving, 1.14g of N, N-dimethylaniline (DMA) was added dropwise, and the mixture was stirred and reacted at room temperature for 3 hours. The addition amount of BPO and DMA was 2wt% of the total mass of tetrabromobisphenol A bisallyl ether (TBPA) and 2-vinyl-4,6-diamino-1,3,5-triazine (VDT). After the reaction was completed, methanol washing and vacuum drying were carried out as in Example 1.

[0067] (2) Preparation of highly heat-resistant and flame-retardant polyurethane optical resin

[0068] At room temperature, add 0.015g of catalyst dibutyltin dichloride, 0.05g of ultraviolet absorber UV-329, 0.1g of internal release agent, 52g of m-xylylene diisocyanate (XDI), and 0.2g of PTBPA-PVDT copolymer into a stirred reaction vessel, and mix and dissolve. Then, add 48g of 2,3-dithio (2-mercapto)-1-propanethiol and mix them to form a raw material composition. After filtering the raw material composition through a filter membrane, inject it into a special mold for lens processing (the liquid level of the raw material composition in the mold is about 7mm), and degas for 1 hour at 2kPa or less and 25°C. The pore size of the filter membrane is 1μm.

[0069] After degassing, the temperature was raised from 25°C to 120°C in an oven to polymerize and cure, and the heating rate was set to 0.2°C / min. When the oven temperature reached 120°C, it was maintained for 2 hours to obtain a cured sample. The sample was then naturally cooled to room temperature, and after secondary curing at room temperature for 48 hours, it was demolded to obtain an optical resin material.

[0070] Example 4

[0071] A highly heat-resistant and flame-retardant polyurethane optical resin containing 7 wt % PTBPA-PVDT copolymer (the monomer molar ratio of TBPA to VDT is 4:1) was prepared.

[0072] (1) Synthesis of PTBPA-PVDT polymer.

[0073] 24.96g of tetrabromobisphenol A bisallyl ether (TBPA) and 1.37g of 2-vinyl-4,6-diamino-1,3,5-triazine (VDT) were added to a reaction vessel in sequence, and then 66g of dimethyl sulfoxide (DMSO) was added as a solvent, and the monomers were completely dissolved by stirring at room temperature. Then 0.53g of dibenzoyl peroxide (BPO) was added to the mixed solution, and after stirring and completely dissolving, 0.53g of N, N-dimethylaniline (DMA) was added dropwise, and the mixture was stirred and reacted at room temperature for 3 hours. The addition amount of BPO and DMA was 2wt% of the total mass of tetrabromobisphenol A bisallyl ether (TBPA) and 2-vinyl-4,6-diamino-1,3,5-triazine (VDT). After the reaction was completed, methanol washing and vacuum drying were carried out as in Example 1.

[0074] (2) Preparation of highly heat-resistant and flame-retardant polyurethane optical resin

[0075] At room temperature, 0.05 g of catalyst dibutyltin dichloride (DBS), 0.05 g of ultraviolet absorber UV-329, 0.1 g of internal release agent, and cyclohexane dimethylene diisocyanate (H 6 XDI) 47.8g, PTBPA-PVDT copolymer 7g, mixed and dissolved. Then, 28.4g 2,3-dithio (2-mercapto)-1-propanethiol and 23.8g tetrakis (3-mercaptopropionic acid) pentaerythritol ester were added in sequence and mixed to form a raw material composition. The raw material composition was filtered through a filter membrane and injected into a special mold for lens processing (the liquid level of the raw material composition in the mold was about 7mm), and degassed for 1 hour at 2kPa or less and 25°C. The pore size of the filter membrane pores was 1μm.

[0076] After degassing, the sample was heated from 25°C to 120°C in an oven to polymerize and cure, and the heating rate was set to 0.1°C / min. When the oven temperature reached 120°C, it was maintained for 2 hours to obtain a cured sample. The sample was then naturally cooled to room temperature, and after secondary curing at room temperature for 48 hours, it was demolded to obtain an optical resin material.

[0077] Example 5

[0078] A highly heat-resistant and flame-retardant polyurethane optical resin containing 0.8 wt % PTBPA-PVDT copolymer (the monomer molar ratio of TBPA to VDT is 12:1) was prepared.

[0079] (1) Synthesis of PTBPA-PVDT polymer.

[0080] 37.44g of tetrabromobisphenol A bisallyl ether (TBPA) and 0.685g of 2-vinyl-4,6-diamino-1,3,5-triazine (VDT) were added to a reaction vessel in sequence, and then 95g of dimethyl sulfoxide (DMSO) was added as a solvent, and the monomers were completely dissolved by stirring at room temperature. Then 0.76g of dibenzoyl peroxide (BPO) was added to the mixed solution, and after stirring and completely dissolving, 0.76g of N, N-dimethylaniline (DMA) was added dropwise, and the mixture was stirred and reacted at room temperature for 3 hours. The addition amount of BPO and DMA was 2wt% of the total mass of tetrabromobisphenol A bisallyl ether (TBPA) and 2-vinyl-4,6-diamino-1,3,5-triazine (VDT). After the reaction was completed, methanol washing and vacuum drying were carried out as in Example 1.

[0081] (2) Preparation of highly heat-resistant and flame-retardant polyurethane optical resin

[0082] At room temperature, 0.05 g of catalyst dibutyltin dichloride (DBS), 0.05 g of ultraviolet absorber UV-329, 0.1 g of internal mold release agent, 23 g of hexamethylene diisocyanate (HDI), and 23 g of cyclohexane dimethylene diisocyanate (HDI) were added into a stirred reaction vessel. 6 XDI) 15.5g, isophorone diisocyanate (IPDI) 11.5g, PTBPA-PVDT copolymer 0.8g, mixed and dissolved. Then, 38g 2,3-dithio (2-mercapto)-1-propanethiol and 12g tetrakis (3-mercaptopropionic acid) pentaerythritol ester were added in sequence and mixed to form a raw material composition. The raw material composition was filtered through a filter membrane and injected into a special mold for lens processing (the liquid level of the raw material composition in the mold was about 7mm), and degassed for 1 hour at 2kPa or less and 25°C. The pore size of the filter membrane was 1μm.

[0083] After degassing, the sample was heated from 25°C to 120°C in an oven to polymerize and cure, and the heating rate was set to 0.1°C / min. When the oven temperature reached 120°C, it was maintained for 2 hours to obtain a cured sample. The sample was then naturally cooled to room temperature, and after secondary curing at room temperature for 48 hours, it was demolded to obtain an optical resin material.

[0084] Comparative Example 1: Preparation of polyurethane optical resin material without PTBPA-PVDT Compared with Example 1, this comparative example does not add the homemade PTBPA-PVDT copolymer, and the other sample types and amounts, experimental steps and reaction time are the same as those in Example 1.

[0085] Comparative Example 2: Preparation of polyurethane optical resin material without PTBPA-PVDT Compared with Example 4, this comparative example does not add the homemade PTBPA-PVDT copolymer, and the other sample types and amounts, experimental steps and reaction time are the same as those of Example 4.

[0086] In order to further illustrate the technical advancement of the present invention, experimental tests are now conducted on indicators of different embodiments and comparative examples.

[0087] Flame retardant performance test of materials: The optical resin lens materials of Examples 1-5 and Comparative Examples 1-2 were tested for LOI values ​​of different resins according to GB / T2406.2-2009. The above test data are listed in Table 1.

[0088] Optical performance test: The optical resin lens materials of Examples 1-5 and Comparative Examples 1-2 were tested for light transmittance (transmittance) and YI value, respectively. The above test data are listed in Table 1.

[0089] Thermal performance test: The optical resin lens materials of Examples 1-5 and Comparative Examples 1-2 were tested for glass transition temperature Tg using differential scanning calorimetry (DSC), and each sample was tested 3 times in parallel to obtain the average value. The sample Tg test data is shown in Table 1.

[0090] Table 1 Test values ​​of optical resin lens material properties in Examples 1-5 and Comparative Examples 1-2

[0091]

[0092] According to the results of Examples 1-5 and Comparative Examples 1-2, the high heat-resistant flame-retardant polyurethane optical resin obtained by the preparation method of the present invention not only has a higher LOI value and Tg, but also has no negative impact on the optical properties. Therefore, according to the preparation method of the present invention, a high heat-resistant flame-retardant polyurethane resin with excellent performance can be prepared.

[0093] The above-described embodiments are only some embodiments of the present invention, but not all embodiments. Under the guidance of this specification, those skilled in the art may make some modifications or adjustments to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A highly heat-resistant flame-retardant polyurethane resin, characterized in that: The flame retardant polymer is prepared by copolymerizing tetrabromobisphenol A bisallyl ether monomer and 2-vinyl-4,6-diamino-1,3,5-triazine monomer.

2. The polyurethane resin according to claim 1, characterized in that The flame retardant polymer is prepared by dissolving tetrabromobisphenol A bisallyl ether monomer and 2-vinyl-4,6-diamino-1,3,5-triazine monomer in an organic solvent, and then performing free radical polymerization under the condition of a free radical initiator; Preferably, the molar ratio of tetrabromobisphenol A bisallyl ether monomer to 2-vinyl-4,6-diamino-1,3,5-triazine monomer is 1:1-20:1, preferably 3:1-15:1, and more preferably 5:1-10:

1.

3. The polyurethane resin according to claim 1 or 2, characterized in that The free radical initiator is an organic peroxide compound initiator, an azo compound initiator, a redox system initiator or a photosensitive initiator; Preferably, the organic peroxide compound initiator is selected from dibenzoyl peroxide or peroxydicarbonate, the azo compound initiator is selected from azobisisobutyronitrile or azobisisoheptanenitrile, the redox system initiator is selected from an organic oil-soluble redox system formed by a peroxide acyl compound and a tertiary amine compound, and the photosensitive initiator is selected from the photoinitiator IRGACURE-2959; Preferably, the added amount of the initiator is 1% to 6% of the total weight of the tetrabromobisphenol A bisallyl ether TBPA monomer and the 2-vinyl-4,6-diamino-1,3,5-triazine VDT monomer; Further preferably, the free radical initiator is a composite initiator of dibenzoyl peroxide and N,N-dimethylaniline, and the addition amount of both is 1%-3%, preferably 1.5-2.5%, of the total weight of TBPA monomer and VDT monomer.

4. The polyurethane resin according to any one of claims 1 to 3, characterized in that The reaction temperature is 0°C to 50°C, and the reaction time is 1 to 12 hours; Preferably, the organic solvent includes, but is not limited to, one or more of halogenated hydrocarbons, ketones, ethers, alcohols, amides, and sulfones, preferably dimethyl sulfoxide.

5. The polyurethane resin according to any one of claims 1 to 4, characterized in that Also included are an isocyanate component, a polythiol compound, an optional catalyst, an optional mold release agent, and an optional ultraviolet absorber.

6. The resin according to any one of claims 1 to 5, characterized in that The isocyanate component is selected from aliphatic, alicyclic or aromatic isocyanates, preferably toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, naphthalene diisocyanate, dimethylbiphenyl diisocyanate, 1,4-cyclohexane diisocyanate, p-phenylene diisocyanate, tetramethyl-m-xylylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, xylylene diisocyanate, cyclohexane dimethylene diisocyanate, norbornane diisocyanate, one or a combination of two or more thereof, further preferably xylylene diisocyanate or cyclohexane dimethylene diisocyanate, more preferably xylylene diisocyanate; Preferably, the polythiol compound is selected from ethylene glycol dimercaptoacetate, 1,2-bis(2-mercaptoethoxy)ethane, di(thioglycolic acid)-1,4-butylene glycol ester, trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tris(2-mercaptoacetate), pentaerythritol tetramercaptoacetate, 2,3-dithio(2-mercapto)-1-propanethiol, tetrakis(3-mercaptopropionic acid)pentaerythritol ester and one or more thereof, preferably 2,3-dithio(2-mercapto)-1-propanethiol or tetrakis(3-mercaptopropionic acid)pentaerythritol ester, more preferably 2,3-dithio(2-mercapto)-1-propanethiol.

7. The resin according to claim 5 or 6, characterized in that The isocyanate component and the polythiol compound are used in an NCO group / SH group molar ratio of 0.8-1.5, preferably a molar ratio of 0.9-1.

1.

8. The polyurethane resin according to any one of claims 5 to 7, characterized in that: The flame retardant polymer is added in an amount of 0.1% to 10% by weight, preferably 0.5% to 8% by weight, more preferably 1% to 6% by weight, based on the total mass of the isocyanate component and the polythiol compound.

9. The polyurethane resin according to any one of claims 5 to 8, characterized in that: The catalyst is an organotin compound; Preferably, the amount of the catalyst added is 0.001 to 2.0 wt %, preferably 0.005 to 1.0 wt %, based on the total mass of the isocyanate component and the polythiol compound; Preferably, the ultraviolet absorber is a benzophenone, triazine or benzotriazole ultraviolet absorber, and the added amount is 0.001-2.0 wt %, preferably 0.01 to 1.0 wt %, based on the total mass of the isocyanate component and the polythiol compound; Preferably, the release agent is a phosphate-based release agent, and the added amount is 0.01-3.0 wt %, preferably 0.05 to 2.0 wt %, based on the total mass of the isocyanate component and the polythiol compound.

10. A method for preparing the polyurethane resin according to any one of claims 1 to 9, characterized in that: The isocyanate component, the polythiol compound, the flame retardant polymer, the optional catalyst, the optional mold release agent and the optional ultraviolet absorber are mixed and then subjected to polymerization reaction to prepare the product.

Citation Information

Patent Citations

  • Halogen-free flame-retardant optical resin

    CN105778094A

  • Tetrabromobisphenol A diallyl ether-styrene copolymerization flame retardant and preparation method thereof

    CN111635475A

  • Anti-fog heat-resistant polyurethane optical resin and preparation method thereof

    CN116239883A

  • Dental Composition Containing Si-H Functional Carbosilane Components

    US20070238803A1

  • Bis(2,3-dibromopropyl carbonates) of tetrahalobisphenol A

    US3931274A